“Lela” Penerapan Program Lele Keluarga Sebagai Upaya Pencegahan Meningkatnya Kasus Stunting Di Kabupaten Jember: Dony Setiawan Hendyca Putra, Mochammad Choirur Roziqin, Rindiani - Dony Setiawan Hendyca Putra; Mochammad Choirur Roziqin; Rindiani Rindiani (Politeknik Negeri Jember, 2022)
Problems based on a preliminary study conducted by the proposer at the Posyandu in Kemuning Lor Village, it was found that there were 112 children under five who experienced stunting in Kemuning Lor Village. Lack of knowledge of mothers about health and nutrition before and during pregnancy and after childbirth. The economic level of the people of Kemuning Lor Village is classified as lower middle class. This has pushed Kemuning Lor village to become a village that is prone to increasing stunting cases in toddlers. Behind the problems in Kemuning Lor Arjasa Village, there is a positive potential, namely that the water source in the area is very abundant and clear and easy to obtain by residents because it comes from mountain springs. The majority of the people's occupations there are ranchers and farmers. This strongly supports the proposing team in carrying out community service to provide socialization and training as well as direct practice on family catfish cultivation as an effort to improve the community's economy and to prevent the increase in stunting cases in Jember district